The Legislature and Representative Government in Ogun State Nigeria, 1999 - 2011 (2015)
In spite of their critical role and strategic importance as a check on the executive and a bridge between the government and the people, sub-national legislatures have remained largely understudied in Nigeria. This study, therefore, examined the performance of the Ogun State legislature in law-making, representation and oversight, as one of the most volatile and conflictual legislatures in Nigeria between 1999 and 2011. The theory of institutionalisation focusing on autonomy, internal complexity, and universalism provided the conceptual framework. Case study, household survey and exploratory designs were adopted. Structured questionnaire was administered to 424 informed residents of the 1,958,863 voting age population who are able to evaluate the legislature in the three senatorial zones of the state determined by Bernoulli sampling formula. The questionnaire was administered proportionally across fifty-three political wards purposively selected through a two-staged stratified sampling method, covering both urban and rural areas. The questionnaire focused on legislative performance, representation, and oversight. Fifteen in-depth interviews (IDIs) were conducted with political, community and opinion leaders, and legislators on legislature-executive relations, available resources and character of the legislature. Secondary data on constitutional powers, number and types of bills passed were drawn from the assembly, libraries and media reports. Quantitative data were analysed using descriptive statistics, while qualitative data were content analysed. Respondents’ age was 35±8.5, 65.4% males, 65.4% had tertiary education and 61.4% resided in the urban areas. Many respondents, 60%, indicated that the fourth (1999-2003); fifth (2003-2007); and sixth (2007-2011) legislatures performed poorly in constituency relations, and deploying oversight tools like public hearing, inquiry, debate, and visitation. Eighty two per cent of respondents claimed they were never consulted by their representatives. Some 75% of rural respondents were indifferent; whereas 70% of urban respondents opined the legislature was generally ineffective in oversight. To enhance autonomy, the fifth legislature passed two laws that could not be implemented: a law for the establishment of the House of Assembly Service Commission, and a Self-Accounting law. The legislature depended on the executive for financial and human resources. Executive dominance, lack of expertise and facilities, political will, cohesion, and the passivity of a disenchanted citizenry were perceived to have adversely affected the legislature. The legislature experienced high turnover of membership and leadership. It moved regressively from being marginal in the fourth, to rubber stamp in the fifth, embroiled in internal crisis and ultimately became fragmented in the sixth assembly. The sixth assembly had three speakers, disregarded due process, and was immersed in conflicts over allegiance to the governor, involving accusations and counter accusations of cultic oath-taking. Excluding money bills, the legislature was ineffective in law-making as most bills passed into laws were executive initiated. The fourth legislature passed 30 bills; the fifth 50; and the sixth 51 bills. Eighteen, 33, and 28 of these bills were executive bills respectively. Ogun State legislature suffered from executive dominance, as it could not advance its organizational work process, and was ineffective in representation and oversight. The legislature should seek autonomy in human and material resources to become effective.